Metrics of progress in the understanding and management of threats to Australian birds. Issue 2 (22nd November 2018) - Garnett, S. T.; Butchart, S. H. M.; Baker, G. B.; Bayraktarov, E.; Buchanan, K. L.; Burbidge, A. A.; Chauvenet, A. L. M.; Christidis, L.; Ehmke, G.; Grace, M.; Hoccom, D. G.; Legge, S. M.; et al.
Abstract: Although evidence‐based approaches have become commonplace for determining the success of conservation measures for the management of threatened taxa, there are no standard metrics for assessing progress in research or management. We developed 5 metrics to meet this need for threatened taxa and to quantify the need for further action and effective alleviation of threats. These metrics (research need, research achievement, management need, management achievement, and percent threat reduction) can be aggregated to examine trends for an individual taxon or for threats across multiple taxa. We tested the utility of these metrics by applying them to Australian threatened birds, which appears to be the first time that progress in research and management of threats has been assessed for all threatened taxa in a faunal group at a continental scale. Some research has been conducted on nearly three‐quarters of known threats to taxa, and there is a clear understanding of how to alleviate nearly half of the threats with the highest impact. Some management has been attempted on nearly half the threats. Management outcomes ranged from successful trials to complete mitigation of the threat, including for one‐third of high‐impact threats. Progress in both research and management tended to be greater for taxa that were monitored or occurred on oceanic islands. Predation by cats had the highest potential threat score. However, there has been some success reducing the impact of cat predation, so climate change (particularly drought), now poses the greatest threat to Australian threatened birds. Our results demonstrate the potential for the proposed metrics to encapsulate the major trends in research and management of both threats and threatened taxa and provide a basis for international comparisons of evidence‐based conservation science. Abstract : Article impact statement : Quantification of needs and achievements in research and management will help conservation funders and practitioners prioritize investment and action.